Transuterine infection by Baylisascaris transfuga: Neurological migration and fatal debilitation in sibling moose calves (Alces alces gigas) from Alaska. Issue 3 (December 2018) - Hoberg, Eric P.; Burek-Huntington, Kathleen; Beckmen, Kimberlee; Camp, Lauren E.; Nadler, Steven A.
Abstract: Larval Baylisascaris nematodes (L3), resulting from transuterine infection and neural migration, were discovered in the cerebrum of sibling moose calves ( Alces alces gigas ) near 1–3 days in age from Alaska. We provide the first definitive identification, linking morphology, biogeography, and molecular phylogenetics, of Baylisascaris transfuga in naturally infected ungulates. Life history and involvement of paratenic hosts across a broader assemblage of mammals, from rodents to ungulates, in the transmission of B. transfuga remains undefined. Neural infections, debilitating young moose, may seasonally predispose calves to predation by brown bears, facilitating transmission to definitive hosts. Discovery of fatal neurological infections by L3 of B. transfuga in mammalian hosts serves to demonstrate the potential for zoonotic infection, as widely established for B. procyonis, in other regions and where raccoon definitive hosts are abundant. In zones of sympatry for multi-species assemblages of Baylisascaris across the Holarctic region presumptive identification of B. procyonis in cases of neurological larval migrans must be considered with caution. Diagnostics in neural and somatic larval migrans involving species of Baylisascaris in mammalian and other vertebrate hosts should include molecular-based and authoritative identification established in a phylogenetic context. Graphical abstract: Image 1 Highlights: Larval Baylisascaris nematodes, demonstrating transuterine infection, were discovered in sibling moose calves from Alaska. Baylisascaris transfuga was identified through morphology, biogeography and molecular phylogenetics. Neural infections in ungulate paratenic hosts may predispose calves to predation by brown bears facilitating transmission. Diagnostics for L3 Baylisascaris in zones of sympatry for multiple species should include molecular-based identification.